Application of Cluster Analysis in Marketing Communications in Small and Medium-Sized Enterprises: An Empirical Study in the Slovak Republic - Ližbetinová, Lenka; Štarchoň, Peter; Lorincová, Silvia; Weberová, Dagmar; Průša, Petr (MDPI AG (Multidisciplinary Digital Publishing Institute), 2019)
Creating an effective marketing strategy according to current trends is a key process needed to achieve sustainable growth that can result in attracting a great number of existing as well as potential customers. Moreover, an enterprise's success is affected by the aforementioned process. The aim of the paper is to determine the clusters of small and medium-sized enterprises operating in the Slovak Republic and the use of marketing communication tools in the future. The research into marketing communications and customer relationship management (CRM) building in companies was carried out in Slovakia in the years 2017 and 2018. In total, 1,009 small and medium-sized enterprises from Slovakia participated in the research. Following a K-means clustering algorithm, three clusters were determined. Descriptive statistics, cluster analysis using K-means clustering, and an analysis of variance (ANOVA) were used to identify no statistically significant difference in terms of the size of enterprises.
Aplikace klastrové analýzy v marketingové komunikaci v malých a středních podnicích: Empirická studie na Slovensku
Keywords: SMEs; marketing communications; marketing communication tools; CRM; customer database; cluster analysis; Malé a střední podniky; marketingová komunikace; marketingové komunikační nástroje; CRM; zákaznická databáze; shluková analýza